Effects of behavioural activation on emotional cognition and mood - Ruzickova, T; Murphy, S (2022)
Depression is one of the leading causes of disability worldwide and its prevalence has increased further during the COVID-19 pandemic. There is a need for effective treatments that can be easily and cheaply disseminated worldwide. Behavioural activation is known to be an effective intervention for depression which can be disseminated by non-specialist practitioners. However, its exact mechanism of action is currently unknown, which impedes our understanding for how to deliver it most effectively.